Effect of the practice environment of nurses on job outcomes and safety climate (Revista Latino-Americana de Enfermagem, 2019)
Objective: to propose and analyze a theoretical model to measure the effect of nurses’ perceptions about the practice environment on safety climate, job satisfaction, intention to stay employed and in the profession, and burnout syndrome. Method: correlational study with probabilistic sample of 465 nurses. In the theoretical model, the dimensions of the nursing practice environment were considered as independent variables and job satisfaction, safety climate, intention to stay employed and in the profession, and burnout were considered the outcome variables. Structural Equation Modeling was the method used in the analysis. Results: small adjustments were made in the model and the dimensions of practice environment predicted job satisfaction (R2 = 43%), safety climate (R2 = 42%) and burnout (R2 = 36%), as well as the intention to stay in the job (R2 = 22%) and in the profession (R2 = 17%). Conclusion: the practice environment showed a strong impact on job satisfaction, safety climate and burnout, with a moderate impact on the intention to stay in the institution and in the profession. The findings can be used to manage ca